PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE TEAMS GAMES TOURNAMENT (TGT) UNTUK MENINGKATKAN MINAT DAN HASIL BELAJAR IPA PADA SISWA KELAS VIIB4 DI MTs DARUL HIKMAH PEKABARU - Rinda Maryola; Yuslim Fauziah; Wan Syafii (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract : The purpose of this research is to increase the interest and learning outcomes VIIb4 grade science students MTs Darul Hikmah Pekanbaru after the implementation of cooperative learning model type Teams Games Tournament (TGT). This study was conducted in April-May 2016. This study is a Class Action Research (CAR) conducted in two siklus.Subjek were students in grade VIIb4 by the number of students 24 orang.Parameter of this study are of interest, learning outcomes (absorption and Mastery learning), awards groups, student activities and activity guru.Hasil research found the average student interest before the implementation of cooperative learning model TGT is 1.80 (Low), increased after the first cycle that 2:03 (Medium), and increased after the second cycle ie 3:26 (High) .Rata average dayaserap students padasiklus I amounted to 78.75% (Enough), meninkat padasiklus II became 85.00% with a (Good). Ketuntasanbelajarindividupadasiklus I is 75.00% category, please, padasiklus II became 87.50% dengankategori Baik.Penghargaan group of the second cycle of the four groups awarded with Great category, the second cycle groups one group was awarded the Super category and three groups received awards by category Hebat.Rata -rata activity of students in the first cycle is 66.55% (Less), padasiklus II is 76.90% with (Enough) .Rata average teacher activity padasiklus I and II cycle of 100% dengankategoriSangat Good. Based on research that has been done, Model Cooperative Learning Teams Games Tournament (TGT) in science teaching can improve learning outcomes siswakelas interest and VIIb4 MTs Darul Hikmah Pekanbaru.Keywords : Cooperative Learning Teams Games Tournamen (TGT), Interests, Learning Outcomes